How voice technologies enhance the customer experience - Edgar, Matthew (O'Reilly Media, 2018)
Whether it's for searching, shopping, getting directions, or playing games, many people today are happy to talk to their devices. A new generation of voice interfaces is offering a new way to perform everyday tasks through a personal connection that's decidedly more human. Tasks such as bank transactions, turning on/off devices and appliances in your house, or even talking to your mirror (yes, there's product for that). This article explains why now is the time to explore ways that voice can enhance your product's user experience--while so many options are still wide open. Matthew Edgar takes you through voice's sudden growth phase and explains how it's inspired many companies to investigate this technology. Are there ways that voice could make interacting with your product more convenient? And more personal?